62.5k views
5 votes
Simplify the expression


(-5+i)/(2i)

User Pengman
by
5.3k points

2 Answers

2 votes

Multiply by the conjugate and simplify.

1/2 + 5i/2

User Starrify
by
5.1k points
5 votes


\text{We know}\ i=√(-1)\to i^2=-1


(-5+i)/(2i)=(-5+i)/(2i)\cdot(i)/(i)=(-5i+i^2)/(2i^2)=(-5i+(-1))/(2(-1))=(-5i-1)/(-2)\\\\=(-5i)/(-2)+(-1)/(-2)=\boxed{(1)/(2)+(5)/(2)i}

User Yegor
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.